2011
DOI: 10.1051/0004-6361/201015532
|View full text |Cite
|
Sign up to set email alerts
|

Study of measured pulsar masses and their possible conclusions

Abstract: We study the statistics of 61 measured masses of neutron stars (NSs) in binary pulsar systems, including 18 double NS (DNS) systems, 26 radio pulsars (10 in our Galaxy) with white dwarf (WD) companions, 3 NSs with main-sequence companions, 13 NSs in X-ray binaries, and one undetermined system. We derive a mean value of M = 1.46 ± 0.30 M . When the 46 NSs with measured spin periods are divided into two groups at 20 milliseconds, i.e., the millisecond pulsar (MSP) group and others, we find that their mass averag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 144 publications
9
121
0
1
Order By: Relevance
“…Such a large mass already argues against significant softening of the equation of state by the emergence of new degrees of freedom at high densities (Özel et al 2010). Mass measurements of a large sample of neutron stars also reveal their intrinsic mass distribution and probe the physics of the supernova explosions and neutron star formation (Thorsett & Chakrabarty 1999;Kiziltan et al 2011;Zhang et al 2011;Özel et al 2012).…”
Section: Complementary Approaches To Neutron Star Physicsmentioning
confidence: 99%
“…Such a large mass already argues against significant softening of the equation of state by the emergence of new degrees of freedom at high densities (Özel et al 2010). Mass measurements of a large sample of neutron stars also reveal their intrinsic mass distribution and probe the physics of the supernova explosions and neutron star formation (Thorsett & Chakrabarty 1999;Kiziltan et al 2011;Zhang et al 2011;Özel et al 2012).…”
Section: Complementary Approaches To Neutron Star Physicsmentioning
confidence: 99%
“…This one-to-one correspondence between the EoS and the mass-radius relation of NSs allows in principle to determine or at least to constrain the EoS from the simultaneous measurement of the mass and the radius of a NS. While NS masses have been measured very precisely in binary systems [1,[5][6][7], the determination of radii has not yet been achieved with high precision (see e.g. [1,2,8,9] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Schwab et al (2010) argued that the distribution of neutron star masses in double neutron stars is actually bimodal, with one peak centered at ∼1.25 M and the other at ∼1.35 M , which they attributed to different supernova explosion mechanisms. Kiziltan et al (2010), Valentim et al (2011), andZhang et al (2011), on the other hand, inferred the mass distribution of different neutron star subgroups based either on the pulsar spin period or the binary companion, both of which were taken to be indicative of the accretion history of the system. All groups found that the neutron stars that are thought to have undergone significant accretion are, on average, 0.2-0.3 M heavier than those that have not.…”
Section: Introductionmentioning
confidence: 99%